The timecourse of collagen cross-linking - Pinto, Jeffrey S.; Peter Bentley, J. (Biochimica et biophysica acta, 1974)
The incorporation of [ 3H] proline into all major denaturation subunits of acid-extractable skin collagen was followed in vivo over a period of 30 days in young male rats. The radioactivity was incorporated into the α 1 and α 2 subunits at an equal rate. It was then transferred to the β subunits, the ratio of specific activity of α:β becoming unity at about 17 days. No transfer of radioactivity from β to γ collagen was seen during the 30 days of the experiment indicating that β units do not cross-link further to γ during this time. A separate group of rats made lathyritic with β-aminopropionitrile showed a similar rate of collagen cross-linking as reflected by the return of α:β ratios to normal values within about 15 days following the cessation of β-aminopropionitrile administration. In the normal rats radioactive proline was incorporated very rapidly into a fraction of collagen eluted from CM-cellulose with 0.5 M NaCl following the salt gradient. It is proposed that this fraction may represent a fibrogenesis nucleation factor.